Kepemimpinan Strategis Kepala Madrasah Sebagai Change Leader - Muhyidin Muhyidin (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2023)
The success of a madrasa in providing quality education, as well as in elevating its profile to a higher level, cannot be separated from the leadership factor of its head. The results of Peters & Austin's research confirms that the factor that determines quality in an institution is leadership. On that basis, this research was conducted to describe the leadership of the madrasa principal which is suspected to be an important part of the process of change that occurs in these Islamic educational institutions. The research was conducted using a qualitative approach with a focus on change leadership, with the subject being the Head of MIN Tempel Sleman, D.I. Yogyakarta, Period 2003–2010. From the results of the study, it was concluded that the changes that occurred at MIN Tempel Sleman were sourced from the leadership's vision and the idea of changing the head of the madrasa. In the process, change is carried out through six strategic steps, namely developing a vision, developing strategic plans and work programs, influencing mindsets and culture, creating agents of change, overseeing the change process, and encouraging innovation and learning.